Mechanism of Action of Fusarium oxysporum CCS043 Utilizing Allelochemicals for Rhizosphere Colonization and Enhanced Infection Activity in Rehmannia glutinosa - Feiyue Yuan; Fuxiang Qiu; Jiawei Xie; Yongxi Fan; Bao Zhang; Tingting Zhang; Zhongyi Zhang; Li Gu; Mingjie Li (Plants)
Rehmannia glutinosa is an important medicinal herb; but its long-term cultivation often leads to continuous cropping problems. The underlying cause can be attributed to the accumulation of and alterations in root exudates; which interact with soil-borne pathogens; particularly Fusarium oxysporum; triggering disease outbreaks that severely affect its yield and quality. It is therefore crucial to elucidate the mechanisms by which root exudates induce F. oxysporum CCS043 outbreaks. In this study; the genome of F. oxysporum CCS043 from R. glutinosa’s rhizosphere microbiota was sequenced and assembled de novo; resulting in a 47.67 Mb genome comprising 16,423 protein-coding genes. Evolutionary analysis suggests that different F. oxysporum strains may adapt to the host rhizosphere microecosystem by acquiring varying numbers of specific genes while maintaining a constant number of core genes.The allelopathic effects of ferulic acid; verbascoside; and catalpol on F. oxysporum CCS043 were examined at the physiological and transcriptomic levels. The application of ferulic acid was observed to primarily facilitate the proliferation and growth of F. oxysporum CCS043; whereas verbascoside notably enhanced the biosynthesis of infection-related enzymes such as pectinase and cellulase. Catalpol demonstrated a moderate level of allelopathic effects in comparison to the other two. Furthermore; 10 effectors were identified by combining the genomic data. Meanwhile; it was found that among the effector-protein-coding genes; ChiC; VRDA; csn; and chitinase exhibited upregulated expression across all treatments. The expression patterns of these key genes were validated using qRT-PCR. Transient overexpression of the two effector-encoding genes in detached R. glutinosa leaves provided further confirmation that ChiC (GME8876_g) and csn (GME9251_g) are key effector proteins responsible for the induction of hypersensitive reactions in R. glutinosa leaf cells. This study provides a preliminary indication that the use of allelochemicals by F. oxysporum CCS043 can promote its own growth and proliferation and enhance infection activity. This finding offers a solid theoretical basis and data support for elucidating the fundamental causes of fungal disease outbreaks in continuous cropping of R. glutinosa and for formulating effective mitigation strategies.